Th e eff ects of fiscal expansion at the zero lower bound of interest rates - Ciżkowicz, Piotr; Rzońca, Andrzej (Journal of Public Governance, 2012)
The following paper analyzes the effects of fiscal expansion at the zero lower bound (ZLB) of interest rates. The analysis uses the New Keynesian framework, which is commonly applied by central banks. The authors demonstrate that monetary policy can be deemed incapable of closing a negative output gap only under certain assumptions. Namely, the central bank must be unwilling or unable to commit to maintain the real interest rate below its natural level for a sufficiently long period, or by sufficient margin after the distortion lowering the natural rate of interest or aggravating financial market frictions fades. Th is kind of inefficiency of monetary policy in stimulating aggregate demand is temporary and may occur especially when the distortion lowering the natural rate of interest or aggravating financial market frictions is not only substantial but also persistent. The authors discuss its implications for efficiency of fiscal expansion, and show that if the distortions, which are the source of monetary policy inefficiency, persist, the probability of effective fiscal expansion diminishes. Against this background, the authors outline the risk the economy can face when fiscal expansion is inefficient at the ZLB, and demonstrate that the expansionary fiscal policy can consolidate the setup of low economic activity at the ZLB, instead of – as frequently argued – improving it.